It Is as Blessed To Receive as It Is To Send - Horace S. Tyler (Journal of Applied Communications, 1985)
Although I was delighted and elated to receive Larry Quinn's phone message that I had been accorded this honor, I also soon faced the reality that I would have to say something significant in response.